Prevalence of diabetes and impaired fasting glucose in Poland—the NATPOL 2011 Study. Issue 12 (22nd July 2014) - Rutkowski, M.; Bandosz, P.; Czupryniak, L.; Gaciong, Z.; Solnica, B.; Jasiel‐Wojculewicz, H.; Wyrzykowski, B.; Pencina, M. J.; Zdrojewski, T.
Abstract Aims The aim of the analysis was to assess the prevalence of diabetes and impaired fasting glucose in Poland. Methods A questionnaire survey on a representative sample of 2411 Polish adults, complemented by blood pressure, anthropometric and fasting plasma glucose measurements. The research was part of the national cross‐sectional NATPOL 2011 Study. Diabetes was assessed as self‐reported (diagnosed) or screened (fasting plasma glucose level ≥ 7 mmol/l, based on one blood draw). Results Total prevalence of diabetes in 2011 was 6.7% (95% CI 5.6–7.9); 6.4% (95% CI 5.0–8.0) in women and 7.0% (95% CI 5.4–8.8) in men and did not change from 2002 (6.8%, 95% CI 95% CI 5.8–7.9). Over one quarter of individuals with diabetes were not aware of having the condition. Obesity, arterial hypertension and male gender were strong predictors of screened diabetes. Total prevalence of impaired fasting glucose in the surveyed population was 15.6% (95% CI 14.0–17.2). Conclusions The prevalence of diabetes in Poland is similar to that observed in other European populations and has not changed over the last decade. The fact that every fourth person with diabetes is unaware of the disease creates important opportunities for screening and detection of the disease.